"Dick Tracy" - Berke, Wm. (William), 1903-1958; Taylor, Eric, 1897-1952; Conway, Morgan, 1903-1981; Jeffreys, Anne; Mazurki, Mike, 1907-1990; Gould, Chester; RKO Radio Pictures; Cinetel Films ([Los Angeles, CA] : RKO Radio Pictures, Inc., 1945)
Dick Tracy is faced with a series of brutal murders in which the victims, all from different social and economic backgrounds, are viciously slashed to pieces. Suspects abound but Tracy, getting a clue that there will be fifteen murders in all, must find the common thread among the victims before more are killed. --
Originally released as motion picture in 1945.
Movie distributed by Cinetel for Digitalia Film Library.
Based on the cartoon strip "Dick Tracy" by Chester Gould.
Morgan Conway, Anne Jeffreys, Mike Mazurki, Jane Greer.
Director of photography, Frank Redman; editor, Ernie Leadlay; music, Roy Webb.
In English or Spanish.
Keywords: Tracy, Dick (Fictitious character) -- Drama; Police films; Feature films; Internet videos; Streaming video